POSISI DAN PERAN GURU DALAM POLA KURIKULUM 2013 - Suprapto, Anas (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
The Changes to a curriculum will undoubtedly continue to occur. The big mission of these changes alone is in order to create a better situation for the out put of education. Such changes substantially in order to strike a balance between the spiritual and social attitudes, curiosity, creativity, cooperation with intellectual and psychomotor abilities. Curriculum 2013 appears to create output that is expected of it. To reach it, one fundamental factor is the maximization of the candidates' professional aptitude of teachers as an important instrument for the success of education. The application of research-based learning can be used to develop self-potential students in this controversial curriculum.Â Keywords: teacher, student, curriculum 2013, research